Animal infrastructures: a more-than-human geography of animals and/in/as nature-based solutions - Welden, EA (2024)
From the reintroduction of beavers for natural flood management to the managed grazing of cattle for biodiversity gain, the inclusion—or use—of nonhuman animals in/as environmental interventions is gaining traction in Britain, often associated with the policy turn towards ‘Nature-based Solutions’ (NbS) to climate change and biodiversity loss. NbS are defined by the IUCN as actions that protect, manage, or restore ecosystems while addressing societal challenges (Cohen-Shacham et al., 2016), often involving humans ‘working with nature’ (Seddon et al., 2021). In this thesis, I build upon my past work on NbS (Welden, 2023; Welden et al., 2021), forming a critique of the NbS concept with animals at the centre and demonstrating how this concept necessarily enrols, enmeshes, and enfleshes certain animals as infrastructure.